Mechanical Coupling between Endoderm Invagination and Axis Extension in Drosophila. - Claire M Lye; Guy B Blanchard; Huw W Naylor; Leila Muresan; Jan Huisken; Richard J Adams; Bénédicte Sanson (PLoS Biology)
How genetic programs generate cell-intrinsic forces to shape embryos is actively studied, but less so how tissue-scale physical forces impact morphogenesis. Here we address the role of the latter during axis extension, using Drosophila germband extension (GBE) as a model. We found previously that cells elongate in the anteroposterior (AP) axis in the extending germband, suggesting that an extrinsic tensile force contributed to body axis extension. Here we further characterized the AP cell elongation patterns during GBE, by tracking cells and quantifying their apical cell deformation over time. AP cell elongation forms a gradient culminating at the posterior of the embryo, consistent with an AP-oriented tensile force propagating from there. To identify the morphogenetic movements that could be the source of this extrinsic force, we mapped gastrulation movements temporally using light sheet microscopy to image whole Drosophila embryos. We found that both mesoderm and endoderm invaginations are synchronous with the onset of GBE. The AP cell elongation gradient remains when mesoderm invagination is blocked but is abolished in the absence of endoderm invagination. This suggested that endoderm invagination is the source of the tensile force. We next looked for evidence of this force in a simplified system without polarized cell intercalation, in acellular embryos. Using Particle Image Velocimetry, we identify posteriorwards Myosin II flows towards the presumptive posterior endoderm, which still undergoes apical constriction in acellular embryos as in wildtype. We probed this posterior region using laser ablation and showed that tension is increased in the AP orientation, compared to dorsoventral orientation or to either orientations more anteriorly in the embryo. We propose that apical constriction leading to endoderm invagination is the source of the extrinsic force contributing to germband extension. This highlights the importance of physical interactions between tissues during morphogenesis.